A Decade of Change in Peritoneal Dialysis in Brazil: Challenges and Perspectives in the Public Health System - Moura-Neto, José A.; Modelli de Andrade, Luís Gustavo [UNESP]; Moura, Ana Flávia; Cruz, Constança Margarida Sampaio (MDPI, 2025)
Background/Objectives: The Brazilian Constitution defines health as a universal right and a State responsibility, with the Unified Public Health System (SUS) ensuring free access to comprehensive care, including renal replacement therapies (RRTs) such as dialysis and kidney transplantation. This study aimed to analyze trends in peritoneal dialysis (PD) usage within Brazil’s public health system over a 10-year period, focusing on geographic, demographic, and clinical changes. Methods: Using data from DATASUS and the Brazilian Society of Nephrology Dialysis Census, we analyzed PD usage and patient characteristics from 2014 to 2023. This methodology enabled an in-depth examination of shifts in RRT trends across regions and patient demographics. Results: PD usage declined from 6.5% in 2014 to 4.3% in 2023, with the steepest reductions observed in the North and Northeast regions. Usage increased in the Central-West region, while the Southeast and South experienced steady declines from 2016 to 2023. The proportion of centers offering PD decreased from 51.6% in 2014 to 37.9% in 2023. Over time, the average age of PD patients increased, as did the proportion of Brown/Black individuals receiving PD. Despite these shifts, patient serum levels of hemoglobin, parathyroid hormone, and phosphorus remained stable. Conclusions: This study highlights a relative decline in PD availability and use within Brazil’s public health system, with notable regional disparities. These findings underscore the urgent need for targeted policies to support PD infrastructure, funding, and training to ensure equitable access to RRT across the country.
Keywords: Brazil; health disparities; health policy; peritoneal dialysis; public health systems; renal replacement therapy